Some Dif f erentiation Rules The following pages list various rules for finding derivatives with very basic examples to show how the rules are used. Note: The following pages are NOT formula sheets for exams or quizzes. Definition: Let f (x) be a function. Then the derivative of f (x) is the function denoted f 0 (x) given by f 0 (x) = lim h→0 f (x + h) − f (x) h PROVIDED this limit exists. For a particular value of x, say x = a, the derivative evaluated at x = a is given by f 0 (a) = f 0 (x) x=a f (a + h) − f (a) h→0 h = lim PROVIDED this limit exists at x = a. A function y = f (x) is differentiable at a if f 0 (a) exists, i.e., if the above limit exists. This value f 0 (a) is called the derivative of f at x = a. Other notations: f 0 (x) df dx d f dx Dx f y0 Dx(2) f y 00 Dx(3) f y 000 Dx(4) f y (4) Dx(n) f y (n) dy dx d y dx Dx y Notations for Higher Order Derivatives: 2nd order: f 00 (x) 3rd order: f 000 (x) 4th order: f (4) (x) nth order: f (n) (x) d2 f dx2 d3 f dx3 d4 f dx4 dn f dxn d2 f dx2 d3 f dx3 d4 f dx4 dn f dxn d2 y dx2 d3 y dx3 d4 y dx4 dn y dxn d2 y dx2 d3 y dx3 d4 y dx4 dn y dxn Dx(2) y Dx(3) y Dx(4) y Dx(n) y The point slope form of the equation of a line with slope m and through the point (x1 , y1 ) is given by y − y1 = m(x − x1 ). We can use this form of the equation of a line to express the equation of the Tangent Line to a curve y = f (x) at the point (a, f (a)) by the equation y − f (a) = f 0 (a)(x − a). The slope of the tangent line to the curve a the point (a, f (a)) is given by the value of the derivative f 0 (x) evaluated at a; so m = f 0 (a). At the point (a, f (a)), x1 = a, and y1 = f (a). The normal line to a curve y = f (x) at the point (a, f (a)) is perpendicular to the tangent line to the 0 curve at that same point. It is given by y − f (a) = f−1 0 (a) (x − a) (provided f (x) 6= 0). The derivative gives the instantaneous rate of change of y = f (x) with respect to x at the instant x = a. If y = f (x) gives the position of a moving particle, then the first derivative f 0 (a) gives the instantaneous velocity of the particle at the instant x = a while the second derivative f 00 (a) gives the instantaneous acceleration of particle at the instant x = a. Example: y = f (x) = x3 + 5x2 , f 0 (x) = 3x2 + 10x. When x = 2, y = f (2) = 28, then f 0 (2) = 32 and the equation of the tangent line y − f (a) = f 0 (a)(x − a) becomes y − 28 = 32(x − 2). 1 Some Dif f erentiation Rules Dif f erentiation Rules b and c are real constants; b > 0, b 6= 1 Examples √ ( 5)0 = 0 (6)0 = 0 1. (c)0 = 0 0 0 (π 2 )0 = 0 0 2. (cx) = c x =1 3. (xn )0 = nxn−1 n = any real number (x8 )0 = 8x7 0 (6x) = 6 1 x5 (πx) = π 0 = x−5 √ 1 1 2 ( 3 x)0 = (x 3 )0 = x− 3 3 4. Sum & Difference Rule: [f (x) ± (x)]0 = f 0 (x) ± g 0 (x)) 5. cf (x) 0 6. (ex )0 = ex (5x2 + ex )0 = 10x + ex 7. (bx )0 = bx ln b (6x)0 = 6x ln 6 8. (ln x)0 = 1 x 9. (logb x)0 = (3 + 2x + ln x)0 = 2 + 1 x ln b = −5x−6 [x3 + 5x]0 = (x3 )0 + (5x)0 = 3x2 + 5 √ √ √ [x8 − 7x]0 = (x9 )0 − ( 7x)0 = 9x8 − 7 (4x2 )0 = 4(x2 )0 = 4(2x) = 8x = cf 0 (x) 0 0 0 x 1 1 = (x) = 5 5 5 (log5 x)0 = (3x7 )0 = 21x6 (3ex )0 = 3ex 1 x 1 x ln 5 10. (sin x)0 = cos x (sin x + ex )0 = cos x + ex 11. (cos x)0 = − sin x (5x + cos x)0 = 5 − sin x 12. (tan x)0 = sec2 x (8x2 + tan x)0 = 16x + sec2 x 13. (sec x)0 = sec x tan x (9x + sec x)0 = 9 + sec x tan x 14. (csc x)0 = − csc x cot x (2x + csc x)0 = 2x ln 2 − csc x cot x 15. (cot x)0 = − csc2 x (4ex + cot x)0 = 4ex − csc2 x 16. Product Rule: [f (x) ∗ g(x)]0 = (x3 sin x)0 = (3x2 )(sin x) + (x3 )(cos x) f 0 (x) ∗ g(x) + g 0(x) ∗ f (x) 0 f (x) 17. Quotient Rule: = g(x) g(x) ∗ f 0 (x) − f (x) ∗ g 0 (x) g 2 (x) 18. Inverse Rule: [f −1 (x)]0 = provided f is differentiable and invertible and f 0 (f −1 (x)) 6= 0. 1 f 0 (f −1 (x)) x3 tan x 2 0 = (tan x)(3x2 ) − (x3 )(sec2 x) tan2 x Chain Rule: If h(x) = f ◦ g(x) = f [g(x)], then h0 (x) = f 0 g(x) ∗ g 0 (x) If h(x) = f [g(x)] we can call f (x) the Outer Function and g(x) the inner function. Then h0 (x) = [Outer 0 (inner)] ∗ (inner)0 Equivalently, if we write y = h(x) = f (u), where u = g(x), then dy dy du = ∗ dx du dx Dif f erentiation Rules w Chain Rule Examples [g(x)n ]0 = [ng(x)n−1 ] ∗ g 0 (x) (sin3 x)0 = [(sin x)3 ]0 = 3(sin x)2 ∗ cos x = 3(sin2 x) ∗ cos x 0 √ 13 0 1 2 3 3 3 5x − 7x = 5x − 7x = 3 (5x3 − 7x)− 3 ∗ (15x2 − 7) [ecos x ]0 = [ecos x ] ∗ (− sin x) [eg(x) ]0 = [eg(x) ] ∗ g 0 (x) [ln g(x)]0 = 1 ∗ g 0 (x) g(x) 1 [logb g(x)]0 = ∗ g 0 (x) [g(x)](ln b) [3sin x ]0 = [3sin x ln 3] ∗ (cos x) 1 0 [ln(cos x)] = ∗ (− sin x) cos x 1 [log5 (tan x)]0 = ∗ (sec2 x) [tan x](ln 5) [sin g(x)]0 = [cos g(x)] ∗ g 0(x) [sin 4x2 ]0 = [cos 4x2 ] ∗ 8x [cos g(x)]0 = [− sin g(x)] ∗ g 0(x) [cos(ln x)]0 = [− sin(ln x)] ∗ [tan g(x)]0 = [sec2 g(x)] ∗ g 0 (x) [tan 9x]0 = [sec2 9x] ∗ (9) [sec g(x)]0 = [sec g(x) tan g(x)] ∗ g 0 (x) [sec x4 ]0 = [sec x4 tan x4 ] ∗ (4x3 ) [csc g(x)]0 = [− csc g(x) cot g(x)] ∗ g 0(x) [csc x7 ]0 = [− csc x7 cot x7 ] ∗ (7x6 ) [cot g(x)]0 = [− csc2 g(x)] ∗ g 0(x) [cot x5 ]0 = [− csc 2 x5 ] ∗ (5x4 ) [bg(x) ]0 = [bg(x) ln b] ∗ g 0 (x) 1 x We use the chain rule in a recursive fashion when we have compound compositions such as m(x) = h ◦ f ◦ g(x) = h f g(x) m0 (x) = h0 [f (g(x))] ∗ f 0 (g(x)) ∗ g 0 (x) Compound Chain Rule Examples: 0 [sin7 (2x3 + 4x)]0 = [sin(2x3 + 4x)]7 = 7[sin(2x3 + 4x)]6 ∗ [cos(2x3 + 4x)] ∗ (6x2 + 4) = [7 sin6 (2x3 + 4x)] ∗ [cos(2x3 + 4x)] ∗ (6x2 + 4) 0 √ 1 0 − 1 1 ecos x = ecos x 2 = ecos x 2 ∗ (ecos x ) ∗ (− sin x) 2 2 2 2 [tan(e4x )]0 = [sec2 (e4x )] ∗ (e4x ) ∗ (8x) 3